2024
DOI: 10.3389/fmed.2023.1278879
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and soluble ST2 as mortality predictive biomarkers in male patients with sepsis-induced cardiomyopathy

Lu Wang,
Wen Dai,
Ruiyao Zhu
et al.

Abstract: Sepsis-induced cardiomyopathy (SIC) is characterized by high mortality and poor outcomes. This study aimed to explore the relationship between testosterone and soluble ST2 (sST2) and all-cause mortality in patients with SIC. Clinical data from SIC patients at Renmin Hospital of Wuhan University from January 2021 and March 2023 were reviewed. Serum testosterone and sST2 were measured at admission. Kaplan–Meier analysis and receiver operative characteristic curve (ROC) were used to estimate the predictive values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The Inverse Association between Testosterone Replacement Therapy and Cardiovascular Disease Risk: A Systematic 20year Review and Meta-Analysis Analysis of Prospective Cohort Studies up to 2023 Author: Borges, Julian Yin Vieira M.D cardiovascular disease or risk factors [3,7,12,18,24]. Additionally, TRT was found to improve ejection fraction [15,19,23], lipid profiles [8,11,17], and other cardiovascular risk factors, such as insulin resistance [14,22] and inflammatory markers [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The Inverse Association between Testosterone Replacement Therapy and Cardiovascular Disease Risk: A Systematic 20year Review and Meta-Analysis Analysis of Prospective Cohort Studies up to 2023 Author: Borges, Julian Yin Vieira M.D cardiovascular disease or risk factors [3,7,12,18,24]. Additionally, TRT was found to improve ejection fraction [15,19,23], lipid profiles [8,11,17], and other cardiovascular risk factors, such as insulin resistance [14,22] and inflammatory markers [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The pooled analysis of 15 RCTs (n = 6,872 participants) [7,14,15,18,22] showed that TRT was associated with a significant 22% reduction in the risk of major adverse…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations